SISTEM PENDUKUKUNG KEPUTUSAN EVALUASI KINERJA KARYAWAN PADA HOTEL JOGJA INN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTHING (SAW) - Navida Shofuro; Asih Winantu (LPPM STMIK El Rahma Yogyakarta, 2022)
The process of evaluating employee performance at Hotel Jogja until now has been carried out subjectively without variables and standard assessment methods and has not used a computerized system resulting in non-objective assessments and the results of the assessment do not reflect the routine performance of employees because the assessment has been affected by bias from the supervisor as the appraiser due to the absence fixed variable standard in performance evaluation. The method that will be used to analyze and calculate in this system is the Simple Additive Weighting method with 6 criteria for assessing attendance, time discipline, work quality, cooperation, attitude or ethics, and attention to guests. This system will be web-based using the PHP programming language and MySQL database as a means of data storage. This system generates a list of performance appraisals from the specified alternatives. The final result of the Simple Additive Weighting method is the best alternative choice for the performance of Hotel Jogja Inn employees.